1998
DOI: 10.1103/physreve.58.6999
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous roughening of wood fractured surfaces

Abstract: Scaling properties of wood fractured surfaces are obtained from samples of three different sizes. Two different woods are studied: Norway spruce and Maritime pine. Fracture surfaces are shown to display an anomalous dynamic scaling of the crack roughness. This anomalous scaling behavior involves the existence of two different and independent roughness exponents. We determine the local roughness exponents ${\zeta}_{loc}$ to be 0.87 for spruce and 0.88 for pine. These results are consistent with the conjecture o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 30 publications
6
106
0
Order By: Relevance
“…For mortar, the geometry can be considered as self-affine only up to length scales of the order of 15 % of the specimen width W [18]. A systematic study of wood samples with various values of W leads to ξ = 0.1 W [17]. Figure 6 displays the variations of the correlation function ∆h(δz) as a function of δz for samples of different widths W .…”
Section: Dependence Of the Statistical Properties On The Sample Widthmentioning
confidence: 99%
See 3 more Smart Citations
“…For mortar, the geometry can be considered as self-affine only up to length scales of the order of 15 % of the specimen width W [18]. A systematic study of wood samples with various values of W leads to ξ = 0.1 W [17]. Figure 6 displays the variations of the correlation function ∆h(δz) as a function of δz for samples of different widths W .…”
Section: Dependence Of the Statistical Properties On The Sample Widthmentioning
confidence: 99%
“…In the transient propagation region of fractures initiated from a straight notch, the amplitude of the roughness is observed to depend at all length scales on the distance to the initiation [16,17,18]. This variation may be described by a so called anomalous scaling law involving a new exponent ζ global > ζ referred as the global roughness exponent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent experiments 43,44 have shown that fracture surfaces could be affected by anomalous scaling. This in turn has been interpreted 45 as the mark of the anisotropy of the roughness exponent measured at large lenght scales.…”
Section: Discussionmentioning
confidence: 99%